2021
DOI: 10.1002/jnr.24860
|View full text |Cite
|
Sign up to set email alerts
|

A common genetic variant in fatty acid amide hydrolase is linked to alterations in fear extinction neural circuitry in a racially diverse, nonclinical sample of adults

Abstract: Poor fear extinction learning and recall are linked to the development of fear‐based disorders, like posttraumatic stress disorder, and are associated with aberrant activation of fear‐related neural circuitry. This includes greater amygdala activation during extinction learning and lesser hippocampal and ventromedial prefrontal cortex (vmPFC) activation during recall. Emerging data indicate that genetic variation in fatty acid amide hydrolase (FAAH C385A; rs324420) is associated with increased peripheral endoc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 116 publications
3
9
0
Order By: Relevance
“…Furthermore, a dysfunction in networks including ACC and AIC has been discussed as a potential transdiagnostic marker in psychiatric disorders [ 25 27 ]. Using a region of interest approach, Zabik et al [ 19 ] found less amygdala activation related to the previously extinguished cue in A-allele carriers, which could be interpreted in line with our findings. However, as Zabik et al [ 19 ] investigated trauma-exposed individuals and memory consolidation was only allowed for only 10 min after conditioning in 45 of 59 subjects, comparability of the studies remains unclear.…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Furthermore, a dysfunction in networks including ACC and AIC has been discussed as a potential transdiagnostic marker in psychiatric disorders [ 25 27 ]. Using a region of interest approach, Zabik et al [ 19 ] found less amygdala activation related to the previously extinguished cue in A-allele carriers, which could be interpreted in line with our findings. However, as Zabik et al [ 19 ] investigated trauma-exposed individuals and memory consolidation was only allowed for only 10 min after conditioning in 45 of 59 subjects, comparability of the studies remains unclear.…”
Section: Discussionsupporting
confidence: 91%
“…However, as Zabik et al [19] investigated trauma-exposed individuals and memory consolidation was only allowed for only 10 min after conditioning in 45 of 59 subjects, comparability of the studies remains unclear. Furthermore, while fear ratings in our study confirmed the validity of our conditioning-extinction-extinction recall paradigm [22], neither skin conductance measures nor subjective fear ratings were presented to demonstrate that the unconditioned stimulus (3D virtual snake striking toward participant's viewpoint) used was indeed suited to induce fear [19]. Following previous studies, the ACC seems to play a major role during fear extinction recall in PTSD patients, who frequently show disturbances in extinction recall and exhibit altered activation of the ACC, the hippocampus, amygdala, and ventromedial prefrontal cortex, as compared to trauma-exposed healthy controls [30][31][32].…”
Section: Faah C385a Snp Group Differences and Neural Extinction Recall Signalingmentioning
confidence: 99%
See 1 more Smart Citation
“…Consistent with a recent investigation among healthy adults ( Zabik et al, 2021 ), our physiological indices of fear learning suggest that both groups (CC vs AA/AC allele carriers) exhibited differential responding to the CS+ vs CS- during acquisition and decreased (and non-differential) responding to CS during extinction, suggesting successful acquisition and extinction learning occurred. However, as was the case with the neuroimaging outcomes, the physiological and cognitive signatures of fear acquisition and extinction learning varied as a function of genetic variation within the FAAH C385 gene.…”
Section: Discussionsupporting
confidence: 91%
“…To date, the majority of research focused on the impact of elevated AEA levels (often due to FAAH genetic variation or administration of FAAH inhibitor) on fear conditioning processes has primarily reported on accelerated extinction learning and enhanced recall, with the majority of investigations (all but Ney et al, 2021b ) being conducted in healthy individuals without a clinical diagnosis such as PTSD ( Dincheva et al, 2015 , Mayo et al, 2020a , Mayo et al, 2020b , Zabik et al, 2021 ). Given that this is the first functional neuroimaging study to examine a clinical population (PTSD), and due to differences in task design, our ability to directly compare and contrast our findings with the existing literature is limited.…”
Section: Discussionmentioning
confidence: 99%